2007
DOI: 10.1136/oem.2006.029306
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of ozone air pollution on ischaemic stroke occurrence: a case-crossover analysis from a 10-year population-based study in Dijon, France

Abstract: Objective: To evaluate the association between air pollutants and the occurrence of acute stroke from 10-year population-based study. Methods: The daily stroke count was obtained from Dijon Stroke Register between March 1994 and December 2004. The register recorded all first-ever strokes among residents of Dijon (150 000 inhabitants) in France, using standard diagnostic criteria. Pollutant concentrations (SO 2 , CO, NO 2, O 3 and PM 10 ) were measured hourly. A bi-directional case-crossover design was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
149
2
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(164 citation statements)
references
References 42 publications
(47 reference statements)
7
149
2
6
Order By: Relevance
“…A large case-crossover study found an association between other components of air pollution (NO2 and CO) and cerebrovascular disease, but no correlation was noted with changing PM levels [89]. Similarly, a large registry of first-ever strokes found no association with PM 10 for ischemic or hemorrhagic stroke [90].…”
Section: Pm and Cerebrovascular Health Effectsmentioning
confidence: 99%
“…A large case-crossover study found an association between other components of air pollution (NO2 and CO) and cerebrovascular disease, but no correlation was noted with changing PM levels [89]. Similarly, a large registry of first-ever strokes found no association with PM 10 for ischemic or hemorrhagic stroke [90].…”
Section: Pm and Cerebrovascular Health Effectsmentioning
confidence: 99%
“…1 Several studies have examined the acute effects of outdoor air pollution on stroke using daily time series and case-crossover study designs. [2][3][4][5][6][7][8][9] Although a number of these studies have examined mortality and others have used hospital admissions as a proxy for incident cases, a few have used population case registers, which aim to capture all incident cases. 4,5 A number of these acute effects studies have reported associations between outdoor air pollutants and ischemic stoke, 4,6,7 whereas others have also reported associations with hemorrhagic stroke.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Although a number of these studies have examined mortality and others have used hospital admissions as a proxy for incident cases, a few have used population case registers, which aim to capture all incident cases. 4,5 A number of these acute effects studies have reported associations between outdoor air pollutants and ischemic stoke, 4,6,7 whereas others have also reported associations with hemorrhagic stroke. 8,9 In contrast, although there is an increasing number of studies examining the effects of chronic exposure to outdoor air pollution on cardiovascular mortality using cohort study designs, 10 few have specifically examined stroke mortality.…”
mentioning
confidence: 99%
“…We have identified 18 studies, which fulfilled these criteria (Table 4). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] ACUTE EFFECTS OF PARTICULATE MATTER EXPOSURE Although most studies on PM and cardiovascular diseases have been conducted in developed western countries, first impulses for epidemiologic research on IS came from South Korea and Taiwan. 15,22,25 An increase in PM by an interquartile range in Seoul was associated with a 3% higher IS mortality.…”
Section: Particulate Matter and Human Health Particulate Matter Is A mentioning
confidence: 99%